Simple fabrication of electrochemical sensor based on integration of dual signal amplification by the supporting electrode and modified nanochannel array for direct and sensitive detection of vitamin B2 - Wu, Yafei; Shi, Zhuxuan; Liu, Junjie; Luo, Tao; Xi, Fengna; Zeng, Qi (Frontiers in Nutrition, 2024)
Development of simple and reliable sensor for detecting vitamin content is of great significance for guiding human nutrition metabolism, overseeing the quality of food or drugs, and advancing the treatment of related diseases. In this work, a simple electrochemical sensor was conveniently fabricated by modification a carbon electrode with vertically ordered mesoporous silica thin films (VMSF), enabling highly sensitive electrochemical detection of vitamin B2 (VB2) based on the dual enrichment of the analyte by the supporting electrode and nanochannels. The widely used glassy carbon electrode (GCE), was preactivated using simple electrochemical polarization, The resulting preactivated GCE (p-GCE) exhibited improved potential resolution ability and enhanced peak current of VB2. Stable modification of VMSF on p-GCE (VMSF/p-GCE) was achieved without introducing another binding layer. The dual enrichment effect of the supporting p-GCE and nanochannels facilitated sensitive detection of VB2, with a linear concentration range from 20 nM to 7 μM and from 7 μM to 20 μM. The limit of detection (LOD), determined based on a signal-to-noise ratio of three (S/N = 3), was found to be 11 nM. The modification of ultrasmall nanochannels of VMSF endowed VMSF/p-GCE with excellent anti-interference and anti-fouling performance, along with high stability. The constructed sensor demonstrated the capability to achieve direct electrochemical detection of VB2 in turbid samples including milk and leachate of compound vitamin B tablet without the need for complex sample pretreatment. The fabricated electrochemical can be easily regenerated and has high reusability. The advantages of simple preparation, high detection performance, and good regeneration endow the constructed electrochemical sensor with great potential for direct detection of small molecule in complex samples.